Social Media for Civic Education Engaging Youth for Democracy - Chapman, Amy L. (Palgrave Studies in Educational Media, 2023)
This open access book provides the theoretical and pedagogical foundations for a promising new approach to civic education: using social media to teach civics. While many measures indicate that youth civic engagement has long been in decline, many of these measures fail to take into account all of the ways that youth can interact with civic life. One of these understudied ways is through social media, including platforms like Twitter, where young people have the opportunity to encounter the news, engage with people in power, and bring attention to the needs in their community. Throughout this volume, Chapman explores how and why teachers can use social media to teach civics, as well as how it might meet the needs of students in ways other approaches do not. Amy L. Chapman is Director of the Collaborative for Spirituality in Education and a Fellow in the Clinical and Counseling Psychology Department at Teachers College, Columbia University, USA. Her research interests lie at the intersection of social media, social studies, and social justice, with a particular concern for vulnerable and marginalized students. .